Detection and Analysis of Proteins Modified by O‐Linked N‐Acetylglucosamine. Issue 5 (18th May 2021) - Fahie, Kamau; Narayanan, Bhargavi; Zahra, Fiddia; Reeves, Russell; Fernandes, Steve M.; Hart, Gerald W.; Zachara, Natasha E.
Abstract: O‐GlcNAc is a common post‐translational modification of nuclear, mitochondrial, and cytoplasmic proteins that regulates normal physiology and the cell stress response. Dysregulation of O‐GlcNAc cycling is implicated in the etiology of type II diabetes, heart failure, hypertension, and Alzheimer's disease, as well as cardioprotection. These protocols cover simple and comprehensive techniques for detecting proteins modified by O‐GlcNAc and studying the enzymes that add or remove O‐GlcNAc. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Increasing the stoichiometry of O‐GlcNAc on proteins before analysis Basic Protocol 2 : Detection of proteins modified by O‐GlcNAc using antibodies Basic Protocol 3 : Detection of proteins modified by O‐GlcNAc using the lectin sWGA Support Protocol 1 : Control for O‐linked glycosylation Basic Protocol 4 : Detection and enrichment of proteins using WGA‐agarose Support Protocol 2 : Digestion of proteins with hexosaminidase Alternate Protocol : Detection of proteins modified by O‐GlcNAc using galactosyltransferase Support Protocol 3 : Autogalactosylation of galactosyltransferase Support Protocol 4 : Assay of galactosyltransferase activity Basic Protocol 5 : Characterization of labeled glycans by β‐elimination and chromatography Basic Protocol 6 : Detection of O‐GlcNAc in 96‐well plates Basic Protocol 7 : Assay for OGT activity Support Protocol 5 : Desalting of O‐GlcNAc transferase Basic Protocol 8 : Assay for O‐GlcNAcase activity